Utilization of Natural Materials as Learning Resources for Early Childhood in Group B of Wakeakea Kindergarten, Gu District, Central Buton Regency - Windi Windi (Institute Journal and Publication Muhammadiyah University of Buton, 2023)
The aim of this research is to find out whether researchers using natural materials as learning resources for early childhood can develop children's learning abilities in Wakeakea Kindergarten, Gu District, Central Buton Regency. This research method uses descriptive qualitative methods with data collection techniques using observation, interviews and documentation methods. The first data analysis step is data reduction, the second is presentation of research data grouped based on theme findings and the last is the conclusion. The results of this research are that the use of natural materials as a learning resource for early childhood group B, Wakeakea Kindergarten, Gu District, Central Buton Regency, is very effective in supporting children's learning through 8 learning activities, namely classification and sorting activities, sprinkling activities, weaving activities, collage activities, object counting activities, printing activities and printing activities. And activities using natural materials as learning resources generally develop children's abilities in fine motoric aspects, gross motoric aspects, cognitive aspects, language aspects, social emotional aspects, moral and religious aspects, as well as artistic aspects.